The efficiency of free-floating and emergent aquatic macrophytes in constructed wetlands for the treatment of a fishpond effluent - Osti, João A. S. [UNESP]; Henares, Matheus N. P. [UNESP]; Camargo, Antonio F. M. [UNESP] (Hindawi, 2018)
Many studies have evaluated the efficiency of constructed wetlands (CWs) for the treatment of fishpond effluents, but only a few have compared between CWs with emergent and free-floating macrophytes and assessed the amount of nutrients removed only by the macrophytes. For this purpose, we performed an experiment during 113 days in which we treated a fishpond effluent using four different CWs: (i) with the free-floating macrophyte Eichhornia crassipes (Ec); (ii) without E. crassipes (WEc); (iii) with a substrate and the emergent macrophyte Typha domingensis (Td); (iv) with a substrate and without T. domingensis (WTd). To verify the efficiency of CWs, the removal rates of total suspended solids (TSS), dissolved (DKN) and total (TKN) Kjeldahl nitrogen, total inorganic nitrogen (TIN), total phosphorus (TP) and P-orthophosphate (P-ORT) were analysed using ANOVA-rm. The removal of TP and TKN was higher in CWs with substrate than without substrate. The removal of P-ORT, TIN and DKN was higher in Ec compared to others CWs. The average removal of TSS in Ec (78.9%), WTd (77.4%) and Td (75.0%) was higher than in WEc (68.3%). The contribution of E. crassipes towards the removal of all forms of N and P was higher than of T. domingensis. This greater contribution of E. crassipes can be due to the higher biomass that this species gained in comparison with T. domingensis.
Keywords: Eichhornia crassipes; eutrophication; Nile tilapia wastewater; phytoremediation; Typha domingensis